Decision Support System for Job Applicant Recommendation Using ROC and ORESTE Methods - Mu'arif, Risdani; Putri, Raissa Amanda (Universitas Bina Darma, 2025)
This study developed a Decision Support System (DSS) to assist the employee selection process for an agricultural company located in North Sumatra by utilizing a combination of the Rank Order Centroid (ROC) and ORESTE methods. The system was designed to address the limitations of the manual selection process, which had been time-consuming and inefficient. The ROC method was used to objectively determine the weights of each selection criterion, while the ORESTE method was applied to rank candidates based on their closeness to the company’s ideal profile. The study evaluated ten candidates based on key aspects such as educational background, competencies, work experience, and completeness of documents. The testing results demonstrated that the system was capable of producing accurate rankings consistent with manual calculations and was able to reduce the selection time from approximately two months to just a few minutes. The implementation of this system improved the objectivity and efficiency of the selection process while minimizing the risk of subjectivity in recruitment decision-making.